Dietary quality of school meals and packed lunches: a national study of primary and secondary schoolchildren in the UK - Erin Haney; Jennie C Parnham; Kiara Chang; Anthony A Laverty; Stephanie von Hinke; Jonathan Pearson-Stuttard; Martin White; Christopher Millett; Eszter P Vamos (Cambridge University Press, 2023)
Abstract Objective: School lunches represent a key opportunity to improve diets and health of schoolchildren. No recent nationally representative studies have examined the nutritional differences between school meals and packed lunches in the UK. This study aimed to characterise and compare the nutritional quality of school meals and packed lunches among primary and secondary school-age children. Design: A pooled cross-sectional analysis of the UK's National Diet and Nutrition Survey (2008-2017). Setting: United Kingdom. Participants: 3001 children (aged 4-16 years) who completed a 3/4-d food diary which recorded meal type (school meal/packed lunch). Multivariable logistic regression models assessed associations of meeting food and nutrient recommendations by meal type. Analyses were stratified by academic key stages (KS). Results: KS-1 (4-7 years) and 2 (8-11 years) children consuming school meals were more likely to meet minimum recommendations for vegetables, protein-rich foods and fibre, and not exceed maximum recommendations for salt, savoury and sweet snacks compared with pupils consuming packed lunches. However, in KS-3 (12-14 years) and 4 (14-16 years), these effects were reduced. As children aged, the median weight of fruits, vegetables, protein-rich foods and dairy products consumed typically decreased for both school meals and packed lunches, and generally an increasing proportion of school meals contained sweet and savoury snacks. Conclusion: These findings suggest school meals are nutritionally superior to packed lunches but are not yet optimal. Quality declined at higher KS. Actions to improve lunches of primary and secondary schoolchildren across the UK are needed, with attention to KS-3 and 4 in secondary schools.